Pengembangan Media Ghismi (Game Hijaiyah Simbol Mirip) Terhadap Kemampuan Simbolik Anak Usia 5-6 Tahun Di Tk Puri Cendekia Benowo - Annisatul Ula Dzikra; Kartika Rinakit Adhe; Muhammad Reza; Dewi Komalasari (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to develop and test the feasibility of GHISMI (Similar Symbol Hijaiyah Game) media in improving the symbolic abilities of children aged 5-6 years at Puri Cendekia Benowo Kindergarten, considering that 9 out of 14 children still have difficulty in distinguishing hijaiyah letters that have similar shapes and learning is still limited to the use of LKA (Children's Worksheets) which are less interesting. This study uses the Research and Development method with a 4D development model and produces learning media in the form of audio-visual games containing 12 hijaiyah letters with symbolic similarities. The validation results show that the GHISMI media obtained a feasibility percentage of 90.6% from material experts and 90.3% from media experts with a very feasible category, while the practicality test obtained a percentage of 75% with a practical category. The results of the effectiveness test showed a significant increase in children's symbolic abilities (Sig. 0.000 <0.05) with an N-Gain value of 63% (quite effective category). Research findings show that children become more interested and find it easier to distinguish similar letter symbols because in GHISMI media, children first hear the sound before seeing the letter shape and receive repetition through play activities. This pattern helps children connect sounds and symbol shapes more accurately than learning media that only display letters visually, thus reducing errors in recognizing symbols and improving the symbolic abilities of children aged 5–6 years.